2013
DOI: 10.1590/s1413-70542013000600003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on seed quality in diallel crosses of popcorn

Abstract: The failure to obtain the ideal stand is one of the causes of decreased crop yields, in this sense it is important to investigate the genetic effects related to seed quality. The aim of this study was to measure the general combining ability (GCA), the specific combining ability (SCA) and the reciprocal effects (RE) for popcorn seed quality in addition to evaluate the association between germination and vigor tests with field emergencein order to identify hybrids with better germination and vigour. Ten inbred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
3
7
1
Order By: Relevance
“…The importance of nonadditive effects in traits related to physiological quality of maize seeds were also reported by Gomes et al (2000b), Mortele et al (2011), andCabral et al (2013). The higher estimates of s 2 ŝ for EMERG and NSR suggest that lines from Groups 1 and 2 have contrasting favorable alleles in locus with nonadditive effects for these two traits.…”
Section: Combining Abilitiessupporting
confidence: 69%
See 2 more Smart Citations
“…The importance of nonadditive effects in traits related to physiological quality of maize seeds were also reported by Gomes et al (2000b), Mortele et al (2011), andCabral et al (2013). The higher estimates of s 2 ŝ for EMERG and NSR suggest that lines from Groups 1 and 2 have contrasting favorable alleles in locus with nonadditive effects for these two traits.…”
Section: Combining Abilitiessupporting
confidence: 69%
“…The higher estimates of s 2 ŝ for EMERG and NSR suggest that lines from Groups 1 and 2 have contrasting favorable alleles in locus with nonadditive effects for these two traits. The importance of nonadditive effects in traits related to physiological quality of maize seeds were also reported by Gomes et al (2000b), Mortele et al (2011), andCabral et al (2013).…”
Section: Combining Abilitiessupporting
confidence: 65%
See 1 more Smart Citation
“…Among them, it is worth mentioning Rangel et al (2007) and Vieira et al (2009). On the other hand, Pinto et al (2007), Pajic et al (2008), Silva et al (2010), Viana et al (2011), Vieira et al (2011, Moterle et al (2012) and Cabral et al (2013) stand out when it comes to studies providing information about the diallel cross between popcorn lines.…”
Section: Introductionmentioning
confidence: 99%
“…Moterle et al (2012) studied combining ability for seed quality in nine popcorn strains in a complete diallel without reciprocals, and observed that the estimates of GCA and SCA were significant for germination, first count, accelerated aging, modified cold, electrical conductivity, seedling emergence in sand, speed of emergence, and emergence rate. Cabral et al (2013), in studying the genetic effects of seed quality in diallel in popcorn, found that there was genetic variability for seed quality between strains, where there was a non-additive genetic effect for predominant seed quality, and that there was a prononuced reciprocal effect for seed quality in popcorn, necessitating early indication of male and female parents in crosses.…”
Section: Introductionmentioning
confidence: 99%